2016
DOI: 10.1111/ene.13062
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in myotonic dystrophy type 1: a 5‐year follow‐up study

Abstract: Measurements show that classical/adult onset DM1 is characterized by cognitive decline. Both earlier onset and longer duration of the disease are indicative of more cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 26 publications
6
56
4
2
Order By: Relevance
“…More thorough diagnostic screening procedures may identify less impaired patients with childhood DM1 in earlier stages of the disorder, which might be an explanation of the differences between the countries. [12][13][14] One could speculate that the disorder in children and adolescents with DM1 is a neurodevelopmental disorder, which in older age is supervened by deterioration of cognitive functioning. The VABS assess adaptive functioning from birth through adulthood in a developmental sequence, making it a useful instrument for following development over time, particularly as it also allows comparison of raw scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More thorough diagnostic screening procedures may identify less impaired patients with childhood DM1 in earlier stages of the disorder, which might be an explanation of the differences between the countries. [12][13][14] One could speculate that the disorder in children and adolescents with DM1 is a neurodevelopmental disorder, which in older age is supervened by deterioration of cognitive functioning. The VABS assess adaptive functioning from birth through adulthood in a developmental sequence, making it a useful instrument for following development over time, particularly as it also allows comparison of raw scores.…”
Section: Discussionmentioning
confidence: 99%
“…8 There are reports of a decrease in intellectual abilities in individuals with the congenital form of DM1, 10 as well as reports of a decline in Full-scale IQ in some individuals with the childhood form of DM1. Winblad et al 14 observed a cognitive decline in adultonset DM1, finding that earlier onset and longer duration of the disease were associated with greater cognitive deficits. 4,5 Findings from longitudinal research into the progression of cognitive impairment in adults with DM1 show a worsening of symptoms related to frontal cognitive impairment.…”
mentioning
confidence: 98%
“…A large number of DM 1 patients showed reduced ability to recognize facial expressions in recognition tasks and have difficulty in understanding others' mental states from both interaction with others in everyday situations and from their facial expressions. They are impaired in tests assessing the theory of mind (ToM, ability to infer other people's mental states, thoughts and feelings; Takeda et al, 2009; Kobayakawa et al, 2010, 2012; Masaoka et al, 2011; Winblad et al, 2016). In addition, reduced awareness of disease burden is common (Baldanzi et al, 2016a).…”
Section: Neuropsychiatric Cognitive and Other Neurological Symptomsmentioning
confidence: 99%
“…Very recently, two studies have reported for DM1 patients, a cognitive decline on longitudinal studies of 5 or 9 years especially for verbal memory, attention, visuo-spatial construction, and processing speed (Gallais et al, 2017; Winblad et al, 2016). In particular, the Swedish study showed that cognitive decline in adult DM1 correlated with earlier onset and longer duration of the disease suggesting a degenerative process, while the Canadian study supported the hypothesis of a progeroid disease (accelerated and increased aging process).…”
Section: Progression Of Cns Symptoms With Agementioning
confidence: 99%
“…4 Most DM1 patients will need occupational therapy for equipment as muscle impairment develops. 11,12 The complex nature of DM1 results in various levels of disability, and for many, reduced social participation and independence. Neuropsychiatric symptoms and characteristic cognitive profiles, for instance impaired executive function and global cognitive impairment, are considered part of the disease.…”
Section: Introductionmentioning
confidence: 99%